2019
DOI: 10.1038/s41598-019-48495-5
|View full text |Cite
|
Sign up to set email alerts
|

Latent-period stool proteomic assay of multiple sclerosis model indicates protective capacity of host-expressed protease inhibitors

Abstract: Diseases are often diagnosed once overt symptoms arise, ignoring the prior latent period when effective prevention may be possible. Experimental autoimmune encephalomyelitis (EAE), a model for multiple sclerosis, exhibits such disease latency, but the molecular processes underlying this asymptomatic period remain poorly characterized. Gut microbes also influence EAE severity, yet their impact on the latent period remains unknown. Here, we show the latent period between immunization and EAE’s overt symptom onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 65 publications
6
32
0
Order By: Relevance
“…A major limitation to large-scale adoption of stool metaproteomics has been is its heavily reduced throughput compared to DNA-sequencing. Considering the labor-intensive, multi-day nature of our previously published stool proteomics method, we found that one researcher could reasonably process 25 stool samples per week on average 6,10 . To narrow this gap, we developed our pipeline to rapidly process hundreds of stool samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A major limitation to large-scale adoption of stool metaproteomics has been is its heavily reduced throughput compared to DNA-sequencing. Considering the labor-intensive, multi-day nature of our previously published stool proteomics method, we found that one researcher could reasonably process 25 stool samples per week on average 6,10 . To narrow this gap, we developed our pipeline to rapidly process hundreds of stool samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were prepared as described in Gonzalez et al 6 . Briefly, sample pellets were disrupted using 500 uL 8M urea lysis buffer supplemented with Roche cOmplete protease inhibitor (04693159001 ROCHE) by vortexing.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations